Domestic and Divine : Roman Mosaics in the House of Dionysos - Kondoleon, Christine (Book collections on Project MUSE., 1995)
In this lavishly illustrated volume, Christine Kondoleon conducts us through the House of Dionysos, showing us what its interior decoration discloses about its inhabitants and their time.